Prevalence of potential drug-drug interactions in the intensive care unit of a Brazilian teaching hospital - Aline Teotonio Rodrigues; Rebeca Stahlschmidt; Silvia Granja; Diogo Pilger; Antonio Luis Eiras Falcão; Priscila Gava Mazzola (Universidade de São Paulo, 2017)
Abstract Patients in intensive care unit are prescribed large numbers of drugs, highlighting the need to study potential Drug-Drug Interactions in this environment. The aim of this study was to delineate the prevalence and risk of potential drug-drug interactions between medications administered to patients in an ICU. This cross-sectional observational study was conducted during 12 months, in an adult ICU of a teaching hospital. Inclusion criteria were: prescriptions with 2 or more drugs of patients admitted to the ICU for > 24 hours and age of ≥18 years. Potential Drug-Drug Interactions were quantified and classified through MicromedexTM database. The 369 prescriptions included in this study had 205 different drugs, with an average of 13.04 ± 4.26 (mean ± standard deviation) drugs per prescription. Potential Drug-Drug Interactions were identified in 89% of these, with an average of 5.00 ± 5.06 interactions per prescription. Of the 405 different pairs of potentially interacting drugs identified, moderate and major interactions were present in 74% and 67% of prescriptions, respectively. The most prevalent interaction was between dipyrone and enoxaparin (35.8%), though its clinical occurrence was not observed in this study. The number of potential Drug-Drug Interactions showed significant positive correlations with the length of stay in the intensive care unit, and with the number of prescribed drugs. Acknowledging the high potential for Drug-Drug Interactions in the ICU represents an important step toward improving patient safety and best therapy results.